Measuring Multiple Text Integration: A Review - Primor, Liron; Katzir, Tami (Frontiers in Psychology, 2018)
Multiple text integration is an important skill in modern society, required in heterogeneous situations, across many disciplines and in daily life. It is a complex skill that builds on bottom-up and top-down processes (Britt and Rouet, 2012). As a complex skill it has been measured in the literature using different techniques. To date, the different ways in which researchers have defined and operationalized the term have not been reviewed. Therefore, the aim of this paper is to review how multiple text integration has been theoretically and empirically assessed. The current paper reviews which texts were typically used, which aspects of integration were assessed, and with which scoring rubrics. Finally, we propose that despite the diverse use of tasks, important features of multiple text integration are missing from current research.